2015
DOI: 10.1017/s000711451500416x
|View full text |Cite
|
Sign up to set email alerts
|

Specific serum carotenoids are inversely associated with breast cancer risk among Chinese women: a case–control study

Abstract: Previous epidemiological studies have revealed the anti-cancer effect of dietary circulating carotenoids. However, the protective role of specific individual circulating carotenoids has not been elucidated. The purpose of this study was to examine whether serum carotenoids, including α-carotene, β-carotene, β-cryptoxanthin, lycopene and lutein/zeaxanthin, could lower the risk for breast cancer among Chinese women. A total of 521 women with breast cancer and age-matched controls (5-year interval) were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…These mechanisms include apoptosis, antioxidant, antiinflammation as well as the modulation of multiple molecular events causing carcinogenesis. Range of research studies indicates that the serum carotenoids, including lutein and zeaxanthin, are inversely associated with breast cancer risk among women (Eliassen et al, 2013;Yan et al, 2016). Similar inverse associations are on record between serum concentrations of zeaxanthin and other carotenoids and colorectal neoplasm (Okuyama et al, 2014).…”
Section: Cvds Oxidative Stress Alzheimer's and Cancermentioning
confidence: 81%
See 1 more Smart Citation
“…These mechanisms include apoptosis, antioxidant, antiinflammation as well as the modulation of multiple molecular events causing carcinogenesis. Range of research studies indicates that the serum carotenoids, including lutein and zeaxanthin, are inversely associated with breast cancer risk among women (Eliassen et al, 2013;Yan et al, 2016). Similar inverse associations are on record between serum concentrations of zeaxanthin and other carotenoids and colorectal neoplasm (Okuyama et al, 2014).…”
Section: Cvds Oxidative Stress Alzheimer's and Cancermentioning
confidence: 81%
“…Bioactive components in dietary food or food-derived peptides provide an essential link in health maintenance, promotion, and prevention of chronic diseases, such as cancer (Hernández-Ledesma & Hsieh, 2015). Anticancer effect of dietary circulating carotenoids is surfacing (Milani et al, 2016;Wang et al, 2016;Yan et al, 2016), where bioactive components present in food can simultaneously modulate more than one potential cellular mechanisms. These mechanisms include apoptosis, antioxidant, antiinflammation as well as the modulation of multiple molecular events causing carcinogenesis.…”
Section: Cvds Oxidative Stress Alzheimer's and Cancermentioning
confidence: 99%
“…A pooled analysis of eight prospective studies by Eliassen et al[4] observed significant inverse associations of circulating levels of α-carotene, β-carotene, lutein/zeaxanthin, lycopene, and total carotenoids with the risk of breast cancer. Certain carotenoids exhibited a stronger inverse association with estrogen receptor negative (ER-) than estrogen receptor positive (ER+) tumors [4], although this was not replicated in subsequent studies [7, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…While a few studies have investigated the relationship between serum carotenoid levels and breast cancer risk in premenopausal women [11, 12], the majority of studies have focused on postmenopausal women over the age of 50. With 24% of all breast cancer cases occurring in women under age 50 [13] and breast cancer accounting for 45% of all cancer diagnoses in women aged 25–49 [14], there is a tremendous need to understand modifiable exposures in younger women.…”
Section: Introductionmentioning
confidence: 99%
“…After several acts of quenching, a carotenoid molecule is destroyed [19]. Stress conditions and various acute diseases are always accompanied by the generation of enormous amounts of free radicals [20], which leads to the degradation of antioxidants including carotenoids [21][22][23][24][25]. We may suggest that the same is true for dengue infection [26][27][28].…”
mentioning
confidence: 99%